Paraneoplastic Syndromes of the Nervous System in Patients Suffering from SCLC. A Review of the Recent Literature - Georgiannakis, Emmanouel; Zougou, Theoni; Mavrommatis, Evaggelos (Acta medica academica, 2024)
Background. Paraneoplastic Neurological Syndromes (PNS) constitute a heterogeneous cluster of disease manifestations related to various cancers. Small Cell Lung Cancer (SCLC) is strongly related to PNS. This narrative review conducted a survey in the available PubMed literature to highlight the appearance of PNSs in SCLC cases and discuss published research highlights on the subject so that general practitioners can be acquainted with the medical phenomenon present in SCLC patients. Method. A narrative review of the medical literature was conducted as documentary informative research in the PubMed medical database, combined with a survey of the online e-library Google Books. The key words used were: “Paraneoplastic Neurological Syndromes” and “Small Cell Lung Cancer”. Results. Paraneoplastic syndromes are related to the presence of a malignancy and are not secondary to treatment. Paradoxally, both a malignancy and its therapeutic approach may cause a series of PNSs. Paraneoplastic cerebellar degeneration, motor neuron disorders, peripheral neuropathies, hyponatremia, and syndromes such as myasthenic Lambert-Eaton, ectopic Cushing’s, Stiffman, and Opsoclonus-myoclonus syndrome may also appear in SCLC cases. Diagnosis follows specific criteria, and they are caused by tumor-directed antibodies known as onconeural antibodies. Immunosuppressants, intravenous immunoglobulins, plasma exchange, rituximab, cyclophosphamide, azathioprine, and tocilizumab could be considered as treatment agents. Conclusions. Most patients demonstrate poor PNS treatment results with common relapse. The time for beginning treatment of PNS is discussed. A multidisciplinary team is needed for potentially earlier diagnosis and PNS improvement, better prognosis, and increased overall survival and quality of life.